Cardiovascular adverse effects of targeted antiangiogenic drugs: mechanisms and management. (April 2016) - Sundararajan, Srinath; Kumar, Abhijeet; Poongkunran, Mugilan; Kannan, Arun; Vogelzang, Nicholas J
Anticancer treatment has evolved enormously over the last decade. Drugs targeting receptor tyrosine kinases, VEGFR and EGFR have changed the treatment landscape of certain cancers and have shifted the theme of anticancer therapy toward personalized care. However, these newer agents also come with unique side-effect profiles not seen with conventional chemotherapy including serious cardiovascular adverse effects. Hence, meticulous understanding of the adverse effects is crucial in maximizing clinical benefits and minimizing detrimental effects of these newer drugs. We have reviewed the cardiovascular adverse effects of anti-VEGF therapy in this article.